Developing preservice teachers intuitions about computational thinking in a mathematics and science methods course - Moon, Peter F.; Himmelsbach, Joshua; Weintrop, David; Walkoe, Janet (Journal of pedagogical research, 2023)
Computational thinking (CT) has the potential to enhance learning when integrated into mathematical classroom activities. Teachers are being asked to include CT concepts in their core disciplines; however, there is an open question as to how best to equip teachers to integrate CT into their practice. Oftentimes teacher candidates enter math and science methods courses with emerging ideas of what CT might be but little formal experience with the construct (Yadav et al., 2014). Relatively little is understood about the most effective ways to support candidates’ understanding of CT, and how to support them in integrating CT into disciplinary instruction. In this paper, we describe a novel method of introducing teacher candidates to CT through a five-lesson module within the context of an existing pre-service teacher math and science methods course. We use an Experience First, Formalize Later format inspired by Stats Medic (2018) to help develop teacher candidates’ intuitions around CT primarily through firsthand experience and the roles it can play in their math and science classrooms. This paper presents the instructional materials for this innovative approach for integrating CT into a pre-service mathematics and science methods course. We will also present data from teaching these materials with a cohort of 14 teacher candidates. Collectively, this work contributes a novel strategy for integrating CT into pre-service methods courses and contributes to our understanding of the relationship between CT and the existing disciplines of K-12 math and science, especially as seen by teacher candidates entering the profession.